Green, practical & scalable approach towards the synthesis of valuable α-keto amides using a metal-free catalyst under solvent-free conditions - Bankar, Shubham R.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (New Journal of Chemistry, 2023)
alpha-Ketoamides are very important motifs as they are present in many natural products, drugs & biologically important molecules. We synthesized a very simple, cheap, eco-friendly & reusable glucose-based carbonaceous material (GCM), which showed high performance as a catalyst in the oxidative cross-dehydrogenative coupling (CDC) reaction of alpha-ketoaldehydes with amines for the synthesis of alpha-ketoamides. The GCM catalyst was also very efficient for one-pot two-step synthesis of alpha-ketoamides from alpha-ketoalcohols as well. The GCM catalyst was able to catalyze alcohol oxidation in alpha-ketoalcohols followed by CDC reaction with amines to form alpha-ketoalcohols. The reactions were found to proceed smoothly at a low temperature of 50 degrees C using a green & economical metal-free catalyst under base-free, ligand-free & solvent-free reaction conditions to get the corresponding alpha-ketoamides in good to excellent yields. The results demonstrated that the GCM catalyst showed acidic as well as superior oxidising catalytic activity due to the presence of a carboxylic acid (-COOH) and hydroxyl (-OH)-enriched carbonaceous framework, which enabled the synthesis of important alpha-ketoamide motifs. The applicability of the catalyst was also evaluated for the synthesis of an anti-HIV agent drug molecule. Greener, cheaper & eco-friendly GCM catalyst as well as catalytic process for synthesis of alpha-Keto Amides.

Selective oxidation of biomass derived 5-hydroxymethylfurfural (HMF) to 2,5-diformylfuran (DFF) over spent dry cell battery cathode material (BCM-2) - Ghadge, Sambhaji S.; Bankar, Shubham R.; Jadhav, Vrushali H. (ACS Applied Engineering Materials, 2024)
Widespread use of batteries across the globe generates a huge amount of waste. This work is the first to report spent dry cell (Zn-Carbon) battery cathode material (BCM-2) as a heterogeneous catalyst for selective synthesis of fine chemical 2,5-diformylfuran (DFF). Cathode material was easily separated from spent batteries, and acid leached followed by calcination to obtain black powder that was denoted as BCM-2. The catalyst was characterized using various techniques such as P-XRD, EDAX, SEM, HR-TEM, TGA, XPS, and BET analysis. Superior catalytic activity was shown by the catalyst for selective formation of DFF using molecular O2 as a sole oxidant. The catalyst was found to give excellent HMF conversion of 97% with 98% high selectivity of DFF. The BCM-2 catalyst was easily recycled and reused without any significant loss in its catalytic activity. This is one of the best examples for a sustainable, cost-effective, and highly efficient catalytic system for the synthesis of the value-added chemical DFF.

Graphitic-C3N4/γ-Al2O3 composite catalyst for synthesis of 5-(Hydroxymethyl) furfural from d-Glucose - Kirdant, Swapnali P.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (Energy & Fuels, 2025)
Currently, the synthesis of 5-hydroxymethylfurfural (5-HMF), with high yields and selectivity from different renewable sources, is an important focus in the biomass conversion area. In the present study, a g-C3N4/gamma-Al2O3(1:1) composite catalyst was prepared using graphitic carbon nitride (g-C3N4) and acidic gamma-alumina (gamma-Al2O3), which was evaluated for its catalytic activity in converting sugars, mainly glucose, to 5-HMF. In the g-C3N4/gamma-Al2O3(1:1) catalyst, N-containing groups on g-C3N4 provided basicity and gamma-Al2O3 provided Lewis acidity to the catalyst. The g-C3N4/gamma-Al2O3(1:1) composite catalyst showed superior activity for 5-HMF synthesis compared to gamma-Al2O3 and g-C3N4 alone. The increased acidic and basic properties of the g-C3N4/gamma-Al2O3(1:1) catalyst significantly influenced both glucose-to-fructose isomerization and dehydration of fructose to HMF by increasing the yield of 5-HMF. In addition, the solvent DMSO:water also played an important role in the one-pot conversion of glucose to HMF by minimizing side reactions, which significantly improved the 5-HMF yield. The reaction was optimized for various solvents, temperatures, and catalyst concentrations to get a maximum yield of 91% from glucose with >99% selectivity of crude 5-HMF. Other sugars like fructose, sucrose, and lactose also provided good yields of 5-HMF. The g-C3N4/gamma-Al2O3(1:1) catalyst was stable and was effectively reused for up to four cycles.

One-pot tandem oxidative-wittig olefination of primary alcohols using spent battery material as a heterogeneous catalyst in green solvent GVL - Bankar, Shubham R.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (Catalysis Letters, 2026)
Extensive global utilization of dry cell batteries resulted in generation of huge amount of battery waste. Up-cycling of spent battery waste material as a heterogeneous catalyst is an emerging area of research. Cathode material from spent dry cell battery (Zinc-carbon) was isolated, acid leached and calcined to obtain BCM-2 which was used as a heterogeneous catalyst for one-pot tandem oxidative-Wittig olefination in & upsih;-valerolactone (GVL) a bio-based green solvent at a temperature of 50 degrees C. Reaction was found to proceed smoothly using an economical catalyst and environment friendly conditions to get olefins in good yield up-to 74%. The catalyst was found to be reusable for four cycles. The reaction was carried out two-steps in one pot using spent battery material as a catalyst in GVL as a solvent under mild reaction conditions and the applicability of catalyst was shown in 13 examples. The catalyst's effectiveness was also assessed in synthesis of (E)-3, 4 `, 5-trimethoxy-trans-stilbene, an intermediate for biologically active Resveratol.
Keywords: One-pot; Oxidation; Spent battery; Wittig olefination